2021
DOI: 10.1097/qad.0000000000002741
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected interactions between dolutegravir and folate: randomized trial evidence from South Africa

Abstract: Objective: Dolutegravir exposure at conception was associated with a preliminary signal of increased infant neural tube defect (NTD) risk. As low maternal folate levels are linked with NTDs, we aimed to assess serum folate concentrations in women starting dolutegravir. Design: We analysed serum folate concentrations from stored plasma among women enrolled in the South African ADVANCE trial. Methods: We compared changes in mean serum folate and occurrence of low serum folate (<14.0 nmol/L) at weeks 0, 12 and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Prior works focused on determining relationships between folate levels or transport pathways and DTG-associated birth defects failed to conclusively generate any cause and effect relationships [11,[56][57][58][59]. Exploring alternative mechanisms was required [11,[56][57][58][59]. Herein, for the first time, we show that DTG inhibits MMPs activities in fetal brain during gestation and as such impairs neurodevelopment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Prior works focused on determining relationships between folate levels or transport pathways and DTG-associated birth defects failed to conclusively generate any cause and effect relationships [11,[56][57][58][59]. Exploring alternative mechanisms was required [11,[56][57][58][59]. Herein, for the first time, we show that DTG inhibits MMPs activities in fetal brain during gestation and as such impairs neurodevelopment.…”
Section: Discussionmentioning
confidence: 77%
“…This includes the mechanism(s) of action on the developing CNS [2,[9][10][11][12][13]. Prior works focused on determining relationships between folate levels or transport pathways and DTG-associated birth defects failed to conclusively generate any cause and effect relationships [11,[56][57][58][59]. Exploring alternative mechanisms was required [11,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 406 women living with HIV initiating either a DTG or an efavirenz based regimen found no significant declines in serum folate concentrations associated with DTG treatment. However, a slight decrease was reported at 12 weeks of treatment compared to baseline in those treated with DTG administered with TDF/FTC which recovered to baseline levels by week 24, while an increase in folate levels was seen in those treated with DTG administered with tenofovir-alafenamide/FTC [39]. Although these findings do not indicate suppression of maternal folate status by DTG, in vitro studies have suggested that DTG is a non-competitive inhibitor of FOLR1 [31], which could impair maternal-fetal folate transport.…”
Section: Discussionmentioning
confidence: 89%
“…Beginning with the 2018 Tsepamo report of NTDs amongst pregnant women taking DTG from the time of conception, recent clinical and preclinical reports have identified mixed findings regarding folate delivery and toxicity amongst women taking DTG, with several studies identifying little or no risk. 19 , 20 , 21 , 22 , 24 , 26 , 27 , 35 In contrast, Cabrera et. al.…”
Section: Discussionmentioning
confidence: 96%
“… 19 This early signal prompted concern regarding the safety of DTG use during pregnancy, and led the World Health Organization to temporarily suspend recommendation of DTG in this population. Reassuring follow-up findings from the Tsepamo study and others demonstrated lower rates of NTDs, though in some cases still higher than rates in populations exposed to non-DTG based ART; 20 , 21 , 22 , 23 however as DTG use continues to rise among pregnant women, and women of childbearing age living with HIV, it remains critical to better understand the implications of in utero DTG exposure on fetal development. Recent reports have identified potential interactions between DTG and folate uptake pathways, though the implications of these findings remain unclear, and findings in in vivo models are limited.…”
Section: Introductionmentioning
confidence: 96%